Notes on the spawning habits and early life-history of the oil sardine, Sardinella longiceps Cuv. & Val. - Velappan Nair, R (Indian Journal of Fisheries, 2016)
Our knowledge of the breeding habits and early life-history of the two commercially important pelagic fishes of India, namely, the oil sardine and the mackerel, is very meager, even though investigations on these and allied aspects of their biology were initiated about the beginning of this century. The first attempt to determine the spawning habits and the factors which control the migration of the oil sardine was made by Hornell (1910) who made some general observations and at the same time stressed the need for intensive investigations on the problems connected with the food, life-history and seasonal migration of the oil sardine and the mackerel for the proper development of these two major fisheries.